The Relevance Between Z Generation Lifestyle and Working Model of Startup Business in Information Technology Field - Sasmitoh Rahmad Riady; Rika Apriani; Rita Wahyuni Arifin (Engagement: Jurnal Pengabdian Kepada Masyarakat, 2022)
The purpose of this soft skill seminar in class XII is to foster enthusiasm in improving soft skills and hard skills which will later be used in finding job opportunities, as well as providing an understanding of the work model of startup companies that are very related to the lifestyle of Generation Z. The method used is an educational method by way of fill in seminars to provide an overview of startup companies that are currently developing, as well as provide perspectives on students who will face graduation so that they remain optimistic in finding job opportunities at startups whose work models are related to the generation Z lifestyle. With the similarities between the Gen Z lifestyles With the startup king model, in terms of work, it will be better and will provide excellent career opportunities for Generation Z.